FINANCIAL PERFORMANCE EVALUATION OF PT FAST FOOD INDONESIA TBK THROUGH FINANCIAL REPORT ANALYSIS (2020-2024) - Andre Leonard Sirait; Anjelly Sitorus; Arpul Sianturi; Remigius Obortus Laia (CV Naskah Aceh, 2025)
In an increasingly competitive business landscape, financial performance serves as a key indicator of a company's success in managing its resources. This study evaluates the financial performance of PT Fast Food Indonesia Tbk (owner of the KFC Indonesia brand) using profitability ratios Return on Assets (ROA), Return on Equity (ROE), and Return on Investment (ROI) over the period 2020–2024. The topic was chosen to assess post-pandemic resilience and highlight KFC's significance as a major player in Indonesia's food industry. A qualitative descriptive methodology was employed, analyzing secondary data sourced from official financial reports. The results indicate that 2022 was the weakest year: ROA stood at 2.03%, ROE at 7.30%, and ROI at 22.68%, largely due to the prolonged impacts of COVID-19. However, a steady recovery followed, with 2024 showing marked improvements: ROA rose to 22.62%, ROE surged to 624.94%, and ROI reached 271.86%, reflecting increased efficiency in asset, equity, and investment management. The study concludes that PT Fast Food Indonesia Tbk has successfully navigated the challenges of the pandemic, achieving significant performance improvements that signal positive prospects and offer vital insights for stakeholder decision-making.